The Pediatric Vision Screening Program Performed in Bolzano in 2010: Significance of the Orthoptic Re-Examination. (June 2013) - Bottin, Davide; Waldhauser, Karin; Bertelli, Enrico
Abstract Aim: To analyze results of the vision screening program performed in the Bolzano District and to evaluate the significance of orthoptic re-screening in children with unreliable results. Methods: In 2010, 7772 children, aged 7 months, 3 years, or 5 years, were invited for orthoptic vision screening. Children with unreliable screening findings were re-invited for a second test. In this retrospective study we examined the charts of all children who underwent screening and reported the outcome. Results: A total of 6126 children were examined; 1646 (21.2%) did not attend screening. Of the children tested, 562 (9.2%) showed positive screening results and were referred for ophthalmologic examination. There were 427 (7.0%) children with unreliable results who were re-examined after 3 to 6 months; among them, 307 (71.9%) showed a negative final result and 120 (28.1% of re-examined subgroup, 1.96% of the total) were positive. Conclusions: The large number of unreliable results at the first screening test could be caused by lack of collaboration. The orthoptic re-examination of children with unreliable results may be useful in reducing the amount of false positives.